2009
DOI: 10.1038/onc.2009.85
|View full text |Cite
|
Sign up to set email alerts
|

AKT1 represses gene conversion induced by different genotoxic stresses and induces supernumerary centrosomes and aneuploidy in hamster ovary cells

Abstract: The oncogenic kinase AKT1 is frequently overexpressed or activated in sporadic breast and ovarian cancers. In human breast tumors, we have previously shown that AKT1 represses homologous recombination (HR) induced by one double-strand break (DSB). To further analyze the impact of AKT1 on HR, we ectopically expressed wildtype or mutant forms of AKT1 in a hamster ovary cell line containing an intrachromosomal substrate for monitoring HR. In this cell line, AKT1 repressed HR induced by different genotoxic stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
3
16
1
1
Order By: Relevance
“…Delocalizing BRCA1 and RAD51 to the cytoplasm inhibits the nuclear functions of BRCA1, such as the recruitment to sites of damage after exposure to ionizing radiation and the control of HR. Consistent with the phenotype of cells that are mutated in components of HR, cells overexpressing AKT1 have a higher frequency of supernumerary centrosomes [60]. Furthermore, the AKT1 signaling pathway negatively regulates the expression of BRCA1 mRNA [61].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Delocalizing BRCA1 and RAD51 to the cytoplasm inhibits the nuclear functions of BRCA1, such as the recruitment to sites of damage after exposure to ionizing radiation and the control of HR. Consistent with the phenotype of cells that are mutated in components of HR, cells overexpressing AKT1 have a higher frequency of supernumerary centrosomes [60]. Furthermore, the AKT1 signaling pathway negatively regulates the expression of BRCA1 mRNA [61].…”
supporting
confidence: 53%
“…More directly related to the questions discussed here, the overexpression of AKT1 has been shown to promote the sequestration of BRCA1 and RAD51 to the cytoplasm [38,60]. This sequestration of BRCA1 and RAD51 to the cytoplasm has been observed both in cultured cell lines and in 60% of sporadic breast cancer tumors, in which it is correlated with the level of AKT1 activation [38].…”
mentioning
confidence: 92%
“…Replication forks are routinely inactivated by endogenous stress (17,18); therefore, HR should play an essential role to protect cells against these types of stresses, and HR deficiency should reveal endogenous replication stress. Remarkably, unchallenged HR-deficient (HR − ) cells display both a genome-wide decrease in replication fork speed (19) and a spontaneous increase in the frequency of cells containing extra centrosomes (20)(21)(22)(23)(24)(25)(26)(27)(28). Two hypotheses may account for these two phenotypes.…”
mentioning
confidence: 99%
“…Some metabolic pathways can more or less directly repress HR. This is the • case in p53 (for a review, see Bertrand et al 2004 ) , in the activation of AKT1 (Plo et al 2008 ;Plo and Lopez 2009 ) or in expression of members of the Bc1-2 family (Laulier et al 2011a ) . Other cellular metabolic pathways affecting HR are likely to be discovered.…”
Section: Comments/considerations Regarding Optimization Of Targeted Gmentioning
confidence: 97%
“…Recently, several studies have shown connections between AKT1 and DNA damage response (for a review, see Guirouilh-Barbat et al 2010 ) . In particular, overexpression of AKT1 induces the sequestration of BRCA1 and RAD51 in the cytoplasm, leading to inhibition of HR (Plo et al 2008 ;Plo and Lopez 2009 ) . Taken together, these data underline the importance of HR in protection against breast cancer and reveal that the AKT1 signaling pathway is the missing link between hereditary and sporadic breast cancers.…”
Section: Deregulation Of Hr and Tumor Predispositionmentioning
confidence: 99%